Montelukast and Neuropsychiatric Events in Children: What is the Evidence? - Lima, Raquel (2024)
Childhood asthma is a prevalent chronic illness, and the medication montelukast is frequently used as treatment. However, this drug has been linked to neuropsychiatric events that have potentially fatal outcomes. The objective of this review paper was to evaluate the available evidence on this association between montelukast and neuropsychiatric events in children. From an analysis of 17 articles and 1 clinical guidance standard identified by a bibliographic search method, only 5 fulfilled the previously defined inclusion criteria. These selected studies provide support for the existence of possible occurrences of montelukast-induced neuropsychiatric symptoms among asthmatic pediatric patients administered with the medication. Therefore, healthcare providers need to be informed about these risks while making prescribing decisions for young patients who are taking montelukast or undergoing follow-up care subsequently. More multicenter studies are needed, with robust samples, longer follow-up period and well-defined methodology, to clarify the association of montelukast with neuropsychiatric events in children.